PENATAAN MEKANISME PENYADAPAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 5/PUU-VIII/2010 - Abdul Fadli; Dessy Artina; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The use of wiretapping or interception technology is an act commonly carried out by law enforcement officials or intelligence officials whether it is used as evidence in handling cases in court or intelligence activities. In the decision of the Constitutional Court Number 5 / PUU-VIII / 2010 which granted the petitioners' petition to fully mandate that in carrying out an arrangement it is regulated in the form of a Law, which was issued in 2010 but in its realization it has not been implemented until now. In making this law on wiretapping, it has been slow, until now there has been no synchronous regulation in the wiretapping area, thus detrimental to the constitutional rights of citizens generally.The purpose of this research is to see the Security Policy, Post-Constitutional Court Decision No. 5 / PUU-VIII / 2010 and to see the structuring of the post-Constitutional Court Decision No. 5 / PUU-VIII / 2010. The research focuses on the absence of general regulations governing thoroughly about this tapping.This research is a normative legal research, because it is based on literature research that takes quotes from reading books, literature, or supporting books that have problems which will be assisted by primary, secondary and tertiary data sources. This study uses qualitative data analysis and produces descriptive data.From the results of the research, it is stated that, First, the act of tapping is an act that is legally prohibited, because it is an act that interferes with one's privacy rights. In view of this, the Constitutional Court granted the petitioners' petition in its entirety and mandated the publication of a special law on wiretapping. Second, the absence of a legal umbrella regulating spatial arrangements which is regulated by each institution does not have a strong legal basis. The author's suggestion is, First, it is hoped that before ratifying the Draft Criminal Procedure Code, especially in the field of wiretapping and the Draft Law on Tapping, to check or reassess whether the Draft Law does not harm someone's privacy rights Second, adding to the process of conducting trials that are not open to the public such as trials of children, this is carried out only when proving the results of wiretapping, or it can also be done by pretrial proceedings first. Third, the law on regulation is regulated in a special regulation which is comprehensive and fosters all formal and material aspects.Keywords: Mechanism-Tapping-The Court's Decision